In vivo PET Imaging of Gliogenesis After Cerebral Ischemia in Rats - Ardaya, María; Joya, Ana; Padro, Daniel; Plaza-García, Sandra; Gómez-Vallejo, Vanessa; Sánchez, Mercedes; Garbizu, Maider; Cossío, Unai; Matute, Carlos; Cavaliere, Fabio; Llop, Jordi; Martín, Abraham (Frontiers in Neuroscience, 2020)
In vivo positron emission tomography of neuroinflammation has mainly focused on the evaluation of glial cell activation using radiolabeled ligands. However, the non-invasive imaging of neuroinflammatory cell proliferation has been scarcely evaluated so far. In vivo and ex vivo assessment of gliogenesis after transient middle cerebral artery occlusion (MCAO) in rats was carried out using PET imaging with the marker of cell proliferation 3′-Deoxy-3′-[18F] fluorothymidine ([18F]FLT), magnetic resonance imaging (MRI) and fluorescence immunohistochemistry. MRI-T2W studies showed the presence of the brain infarction at 24 h after MCAO affecting cerebral cortex and striatum. In vivo PET imaging showed a significant increase in [18F]FLT uptake in the ischemic territory at day 7 followed by a progressive decline from day 14 to day 28 after ischemia onset. In addition, immunohistochemistry studies using Ki67, CD11b, and GFAP to evaluate proliferation of microglia and astrocytes confirmed the PET findings showing the increase of glial proliferation at day 7 after ischemia followed by decrease later on. Hence, these results show that [18F]FLT provides accurate quantitative information on the time course of glial proliferation in experimental stroke. Finally, this novel brain imaging method might guide on the imaging evaluation of the role of gliogenesis after stroke.